Kiss of temptation - Hill, Sandra (Fiction writer) (Hill, Sandra (Fiction writer). Deadly angels., 2013)
"For centuries, Ivak Sigurdsson has served the archangel Michael as a vangel -- a viking vampire angel. Ready to demonstrate that he is more than just a libidinous heartbreaker, he agrees to help lawyer Gabrielle Sonnier. But while her problems are in need of serious attention, so is their attraction for one another."--Amazon.com.